2022
DOI: 10.1111/tid.13941
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of surgical site infections among pediatric liver transplant recipients

Abstract: Introduction Surgical site infections (SSI) are a significant cause of morbidity in liver transplant recipients, and the current data in the pediatric population are limited. The goal of this study was to identify the incidence, classification, risk factors, and outcomes of SSIs among children undergoing liver transplantation (LT). Methods A single‐center, retrospective descriptive analysis was performed of patients age ≤18 years undergoing LT between September 2007 and April 2017. SSI identified within the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The same result was observed in our study, with recipients of deceased donor split grafts developing SSIs Surgical revisions, median (IQR) 0.5 (0-1) 1 (0-3) twice as often as recipients of whole or living donor grafts. According to literature, biliary complications are associated with SSIs [10,28]. Thus, SSIs might be effectively reduced by surgery technique, potentially including prevention bundles rather than single measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The same result was observed in our study, with recipients of deceased donor split grafts developing SSIs Surgical revisions, median (IQR) 0.5 (0-1) 1 (0-3) twice as often as recipients of whole or living donor grafts. According to literature, biliary complications are associated with SSIs [10,28]. Thus, SSIs might be effectively reduced by surgery technique, potentially including prevention bundles rather than single measures.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections like bloodstream infections, pneumonia, or surgical site infections (SSIs) are among the most frequent and severe complications after transplantation [10][11][12][13][14][15][16][17] and directly or indirectly cause about half of early postoperative deaths. SSIs occur in about a quarter of all transplant recipients with the clinical presentation ranging from superficial wound infections to intra-abdominal abscess, peritonitis, or infected necrosis leading to sepsis and requiring additional surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated no association between SSIs and 60-d and 1-y mortality. 16,17 Others have demonstrated an association between SSIs and 1-y mortality, 18 and 1-y allograft loss. 18,19 Our study did not find an increased risk of mortality in those who developed SSIs after adjusting for suspected confounders.…”
Section: Discussionmentioning
confidence: 99%